Developing an Arabic Language Curriculum Using Arabiyyah Baina Yaday Auladina as a Learning Resource for Extracurricular Activities: An R&D Study with the 4D Model - Andini Nuraisyah; Muhbib Abdul Wahab; Fatima El Zahraa; Khalid Khamis Farraj (Tadris Al-'Arabiyyah: Jurnal Pendidikan Bahasa Arab dan Kebahasaaraban, 2026)
This study aim to develop and evaluate an Arabic language learning curriculum for the “Harakah Arabiyah” extracurricuar activity using the Arabiyyah Baina Yaday Auladina book as a learning resource, with a focus on speaking skills.The study employed a Research and Development (R&D) method using the 4D model. Data were collected through document analysis, interviews, and questionnaires involving validators, the school principal, the curriculum department, and students. The results indicate that the developed curriculum has a high level of feasibility (88.8%) and received positive responses from both students and teachers. Furthermore, the findings show that the curriculum, which is based on needs analysis and utilizes structured learning resources and a communicative approach, is considered feasible, interactive, and aligned with students’ needs and the school’s vision. n conclusion, this study contributes a model for developing Arabic language learning curricula, particularly in extracurricular settings at the elementary school level, through the integration of relevant and applicable learning resources. Therefore, further research is recommended, especially to examine the effectiveness of the developed curriculum.